PRAKTIK MANAJEMEN LABA UNTUK MENGHINDARI KERUGIAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2012) - Inke Livia; Imam Subekti (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to determine the real earnings management and accrual earnings management by the company to avoid losses through earnings management proxies i.e cash flow from operation, production cost, discretionary expenses, combination real earnings management, short-term accruals and long-term accruals. This study uses the prospect theory. Research samples were 116 companies listed in Indonesia Stock Exchange during 2010-2012. Grouping the sample companies were allegedly identified and unidentified perform earnings management by using the distribution of EPS based on the exchange rate of the rupiah against the USD as investors in Indonesia are more foreign investors. It is different from previous studies because the researcher also tested the effect of IFRS adoption and firm size to proxies of earnings management. The results of the study explained that companies prefer real earnings management than accrual earnings management. Results obtained no effect of IFRS adoption and firm size (SIZE) with earnings management to avoid losses. Keywords:  Real Earnings Management, Accrual Earnings Management, Proxies of Earnings Management, Prospect Theory, Distribution of EPS, Adoption of IFRS, SIZE.